Karakter Peduli Sosial: Komparasi Modul Elektronik dan Paper Modul Kearifan Lokal Ngubat Padi di Sekolah Dasar - Asrial Asrial; Syahrial Syahrial; Dwi Agus Kurniawan; Juwita Saputri (Prosiding Konferensi Nasional Pengabdian Kepada Masyarakat dan Corporate Social Responsibility (PKM-CSR), 2021)
Abstrack The purpose of this study was to compare the application of the print module and the electronic module to see the indicators of the character of social care. This type of research is quantitative research. This study involved two variables, namely learning teaching materials in class with a sample size of 47 students. Data analysis used descriptive and inferential statistics. The character of students' social care can be seen in the application of the electronic module and the print module. The result, from the two teaching materials, the social care character of SD 64/I Muara Bulian students was dominant in the good category, while the social care character of students with the application of the dominant print module was sufficient.